Allergic Granulomatous Contact Dermatitis: A Reaction to Metal Particles Used in Ear Lobe Piercing - Shafi, Saba; Kahwash, Samir B. (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
This is an image-based clinical vignette demonstrating a granulomatous reaction to metal particles used in ear lobe piercing in a teenage girl who presented with bilateral lesions on her ear lobes, clinically thought to be keloids. Microscopic examination showed extensive granulomatous inflammation with rare polarizable metal particles seen on H&E-stained sections. The granulomatous inflammation was disproportionately extensive in comparison with the rarity of metal particles triggering the process. The diagnosis of allergic granulomatous contact dermatitis was rendered. This overreaction phenomenon is typical of granulomatous inflammation and this case demonstrates the importance of examination of granulomatous inflammatory lesions under polarized light, especially in the context of negative staining for infectious agents.
Keywords: allergic granulomatous contact dermatitis; necrotizing granulomatous inflammation; metal particles; polarized light; foreign body